2009
DOI: 10.1111/j.1474-9726.2008.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere uncapping during in vitro T‐lymphocyte senescence

Abstract: SummaryNormal lymphocytes represent examples of somatic cells that are able to induce telomerase activity when stimulated. As previously reported, we showed that, during lymphocyte long-term culture and repeated stimulations, the appearance of senescent cells is associated with telomere shortening and a progressive drop in telomerase activity. We further showed that this shortening preferentially occured at long telomeres and was interrupted at each stimulation by a transitory increase in telomere length. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…In this study of CD8 + T lymphocytes from healthy human donors, we observed age-dependent in vivo accumulation of late-differentiated cells, which were associated with specific changes in cell surface antigens (loss of CD28 and gain of CD57) (20,22), as well as various senescence markers and phenotypes, such as SA-β-gal activity, shortened telomeres (23,33), poor proliferation (21,34), increased HP1-γ foci (29), increased γ-H2AX foci (35), and increased SASPs (8). In these physiologically senescent or near-senescent CD8 + T lymphocytes, Δ133p53 expression was diminished and p53β expression was increased, similar to our previous observations with senescent human fibroblasts in vitro and pathologically induced in vivo senescence in premalignant tumors (15).…”
Section: Discussionmentioning
confidence: 91%
“…In this study of CD8 + T lymphocytes from healthy human donors, we observed age-dependent in vivo accumulation of late-differentiated cells, which were associated with specific changes in cell surface antigens (loss of CD28 and gain of CD57) (20,22), as well as various senescence markers and phenotypes, such as SA-β-gal activity, shortened telomeres (23,33), poor proliferation (21,34), increased HP1-γ foci (29), increased γ-H2AX foci (35), and increased SASPs (8). In these physiologically senescent or near-senescent CD8 + T lymphocytes, Δ133p53 expression was diminished and p53β expression was increased, similar to our previous observations with senescent human fibroblasts in vitro and pathologically induced in vivo senescence in premalignant tumors (15).…”
Section: Discussionmentioning
confidence: 91%
“…Because the presence of TIF is a hallmark of senescent cells 36 and of senescent T lymphocytes in particular, 44 we propose that early stage CLL is associated to accelerated B-lymphocyte senescence. This might result from the accumulation of various telomere dysfunctions in the B-cell lineage, including telomerase and shelterin down-regulation ( 8 and this work).…”
Section: Discussionmentioning
confidence: 95%
“…The cells were then deposited onto positively charged slides, fixed with methanol at Ϫ20°C for 20 min, and rehydrated with phosphate-buffered saline (PBS) for 10 min. Following incubation with Target Retrieval Solution (Dako Cytomation) at 95°C for 40 min, the slides were allowed to cool for 20 min at room temperature and incubated with blocking solution for 1 h (1% cold water fish gelatin, 0.5% Triton X, 0.5% donkey serum in PBS) (9). The slides were subsequently stained with primary antibodies (mouse monoclonal anti-TRF1 from Abcam and rabbit polyclonal anti-53BP1 from Novus Biologicals) at 1:300 dilution in blocking solution at 4°C overnight in a moist chamber.…”
Section: Methodsmentioning
confidence: 99%